Tafsir Ayat-Ayat Konsep Dasar Manajemen Pendidikan - Sehat Harahap, Lia Ariska Ritonga, Rahmat Hidayat (LPPPI Publishing, 2021)
This literature study was conducted to find out: how the basic concept of education management according to the al-quran, which is interpreted by the maudhlu'i method of interpretation. In this research, the research method used is a qualitative research method with a library study approach (library research) and is sourced from various reading books, articles, interpretations and national journals and international journals. The results of this study indicate several verses of the al-quran which explain the basic concepts of education management after using the maudhlu'i interpretation method.